Desenvolvimento de eletrodo modificado com óxido de grafeno reduzido para determinação de 17α-etinilestradiol - Monteiro, Michael Douglas Santos (2021)
17α-ethinylestradiol (EE2) is a synthetic and emerging micropolluting estrogen which, even at low concentrations (order of µg L-1 and ng L-1 ), provides high risks to human health and the environment. In the present work, electrochemical studies were performed with carbon paste electrodes modified with reduced graphene oxide (ErGO) for the voltammetric determination of EE2. The structural and morphological characterizations of rGO were carried out by FTIR, Raman, UV-VIS, MET and MEV, and showed the characteristic formation of nanomaterial, when used ascorbic acid as a reducing agent (rGOA). The electrodes modified with dry reduced graphene oxide (ErGOAs) showed a higher sensitivity than the carbon paste electrode without modification (EPC). Electrochemical analyzes were performed using the Differential Pulse Voltammetry (VPD) technique, associated with the accumulation technique, called Adsorptive stripping voltammetry (AdSV). Where the optimized parameters were BR pH 8.00 buffer, scan rate of 20.0 mV s-1 , pulse amplitude of 100 mV, pulse time of 10.0 ms, accumulation time of 5 minutes, reading cell in situ. After the optimization of the analysis parameters, an analytical curve was generated for the sensor, which presented a linear range from 0.04 to 8.28 μmol L-1 (R2 = 0.9997), with low detection limits (6.79 nmol L-1 ) and quantification (22.60 nmol L-1 ). The reproducibility and repeatability analyzes showed relative standard deviations (DPR/%) of 2.31% and 5.23%, respectively. The sensor was applied for the determination of EE2 in samples of synthetic urine, contraceptive pills and residual water. Excellent recovery values were obtained for urine samples (94.80; 98.73; 104.00%) and contraceptive pills (102.86%), using the interpolation method on the analytical curve and for wastewater the values (95.00; 103.80; 110.10%) were obtained by the standard addition method. The results obtained show that the developed sensor can be used for the identification and quantification in low concentrations of EE2, given the excellent analytical performance presented.